Justification, evaluation and critique in the study of organizations contributions from French pragmatist sociology - Cloutier, Charlotte; Gond, Jean-Pascal; Leca, Bernard 1968- (Research in the sociology of organizations)
Prelims -- Introduction -- Managing organizational pluralism : how individuals navigate moral contradictions and compromise -- Looking at organizations critically : rhetoric, justification and criticism-as-practice -- Reconsidering valuation and evaluation in organizations -- Pushing the boundaries of pragmatic sociology's theoretical agenda -- Index